Peripheral Blood Smear Analysis for Cattle with Foot and Mouth Diseases in Lembang, West Bandung - Septiyani, Septiyani; Majid, Rully Abiyoga; Gradia, Resty; Setiawan, Iyus; Yantini, Puji; Novianti, Arindita Niatazya (Jurnal Medik Veteriner, 2023)
Foot and Mouth Disease (FMD) is an infectious disease that is endemic and has a significant impact on dairy farming in Indonesia. In reducing the impact caused by FMD, proper handling by veterinarians is necessary. The peripheral blood smear can be used as a data reference to give priority to the right treatment for cattle with FMD. This study aimed to describe the appearance of peripheral blood smears in cattle with FMD. The study data were obtained from 15 cattle with FMD at KPSBU Lembang, West Bandung, West Java, Indonesia. The morphological profile of the blood was examined using the peripheral blood smear method. Morphological abnormalities found in the peripheral blood smear of red blood cells were anisocytosis (microcytosis and macrocytosis), poikilocytosis (achanthocytosis and echinocytosis), and hypochromasia. Different morphological abnormalities of leukocytes can be caused by anorexia due to FMD secondary to lack of nutritional intake. To determine an effective and efficient treatment, it is recommended that veterinarians refer to the results of this study.